A randomized trial investigating the impact of response expectancy on the counting blessings intervention: the role of optimism as a moderator - Predatu, Petronela; David, Daniel; Kirsch, Irving; Florean, Ionuț Stelian; Predatu, Răzvan (Frontiers in Psychology, 2024)
Introduction: This randomized controlled trial aimed to address a knowledge gap concerning the mechanisms responsible for the efficacy of gratitude interventions. Specifically, we investigated how various response expectancies (positive, ambiguous + negative, and no expectancy) impact the efficacy of the "counting blessings" intervention in influencing positive and negative emotions. Additionally, the study explores how optimism levels (high, medium, low) interact with these expectancies to influence intervention efficacy. Method: A total of 529 adult volunteers were recruited through social media and randomly assigned to one of three experimental conditions, Positive Condition (PC), Ambiguous + Negative Condition (ANC), No Expectancy Condition (NEC), using a Random Sequence Generator. Of these, 142 participants completed the seven-day counting blessings intervention, and 111 participated in a follow-up assessment one month later. Missing data were addressed using multiple imputation. The main outcomes were changes in positive and negative emotions, with moderation analysis assessing the interaction between optimism levels and response expectancies. The study adhered to the CONSORT guidelines. Results: While no significant interaction was found between experimental conditions and time regarding emotional outcomes (p ˃ .05), moderation analysis revealed differential interactions between optimism levels and expectancies, particularly influencing positive emotions (p < .009). For participants with low optimism, positive emotions significantly increased from post-intervention to follow-up in the PC (t = -2.42, p < .016) and from pre-intervention to post-intervention in the ANC (t = 2.41, p < .018). Participants with medium optimism experienced an increase in positive emotions across all conditions from pre-intervention to follow-up and from post-intervention to follow-up (pₛ < .05). High optimism participants showed an increase in positive emotions from pre-intervention to follow-up and post-intervention to follow-up in the PC (t = 2.09, p < .038 and t = 3.06, p < .003) and NEC (t = -2.76, p < .006 and t = 2.74, p < .007). Conclusions: Our findings emphasize the effectiveness of a brief gratitude journal and underscore the nuanced role of response expectancy, especially in interaction with the initial level of optimism, in enhancing positive emotions. These results hold significance for both theoretical understanding and clinical applications.